PENGARUH KREDIBILITAS TASYA FARASYA TERHADAP NIAT BELI PRODUK FOCALLURE - Dwiartha Cahyani, Ni Made Pramoni; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium, 2020)
A person's credibility affects the communicant to make a product decision. The use of beauty vloggers is easier to influence consumers' psychology because they are individuals who are popular with society. One of the well-known beauty vloggers in Indonesia and has the highest number of subscribers is named Tasya Farasya. Tasya Farasya collaborated with Focallure in creating products by releasing the eyeshadow pallete "THE NEEDS" FOCALLURE X TASYA FARASYA. The purpose1of this study was to explain the.effect.of Tasya Farasya's.credibility. on purchase intention of Focallure products among adolescents in Denpasar City. . The results showed that Tasya Fasrasya's credibility had a positive influence on the purchase intention of focallure products among adolescents in Denpasar City with a value of 0.536 which was classified as moderate with an influence level of 75% with a sample size of 170 respondents.   Keywords : Beauty Vlogger, Credibility,    Hierarchy Effects Model, Source Credibility